2006
DOI: 10.1021/jp067354i
|View full text |Cite
|
Sign up to set email alerts
|

Bulk Modulus and Structural Phase Transitions of Wurtzite CoO Nanocrystals

Abstract: High-pressure behaviors of wurtzite-type hexagonal CoO nanocrystals were investigated by in situ highpressure synchrotron radiation X-ray diffraction measurements up to 57.4 GPa at ambient temperature. It is found that bulk modulus of the hexagonal CoO phase is about 115 GPa at zero pressure. During compression, the hexagonal CoO phase transfers into rocksalt-type cubic phase in the pressure range of 0.8-6.9 GPa. The volume collapse accompanied by the transition was estimated to be about 20%. This is irreversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 22 publications
5
24
0
Order By: Relevance
“…6a. The estimated relative volume collapse for B4 → B1 transition is 20.15% (at P T 06.93 GPa) which is quite close to the experimental value of 20% [15]. The pressure dependence of bulk modulus in ground and high pressure phases has been depicted in Fig.…”
Section: Gansupporting
confidence: 82%
See 2 more Smart Citations
“…6a. The estimated relative volume collapse for B4 → B1 transition is 20.15% (at P T 06.93 GPa) which is quite close to the experimental value of 20% [15]. The pressure dependence of bulk modulus in ground and high pressure phases has been depicted in Fig.…”
Section: Gansupporting
confidence: 82%
“…The pressure induced structural phase transition has been observed experimentally in some semiconducting nanomaterials : ZnO (nanorods), ZnS (2.8, 5, 10 and 25.3 nm), ZnSe (nanoribbons), GaN (2-8 nm), CdSe (4.2 nm), CoO (50 nm), CeO 2 (9-15 nm), SnO 2 (3, 8, 14 nm), SiC (20,30,50, and 130 nm), c-BC 2 N (5-8 nm) and β-Ga 2 O 3 (14.8 ±1.9 nm), using in-situ energy dispersive X-ray diffraction at room temperature [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. The high pressure behavior of two samples of ZnO nanorods with different grain sizes (sample A : diameter 150 nm, length 12000 nm and sample B : diameter 10 nm, length 230 nm) have been studied and compared with their corresponding bulk phase by Xiang et al [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Risbud et al [11] used the thermolytic decomposition of Co(acac) 2 in refluxing benzyl ether to obtain CoO with fcc-Co phase while decomposition of Co(acac) 3 (acac = acetylacetonate) in oleylamine was also applied to synthesize wurtzite CoO [12]. Moreover, different CoO nanocrystals, such as nanoparticles [13][14][15][16], nanorod [17], nanoplatelet [18] have also been reported. However, to our best knowledge, there is no report on the preparation of pure cuspate deltoid CoO crystallites by decomposition of Co 3 O 4 under molten salt atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…It might be underestimated because there is no consideration given to stress. [34] Alivisatos et al reported that the domain size of crystalline CdSe decreases as the system undergoes subsequent transition. [35] A similar result was observed during our hexagonal to cubic transformation.…”
Section: Wurtzite To Rock Salt Structural Transformationmentioning
confidence: 99%